SEGMENTASI PEMAKAIAN INTERNET BROADBAND MENURUT USIA, JENIS KELAMIN, PENDIDIKAN, SEKS DAN PROVIDER INTERNET - Mashur Razak (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
The intensity of usage and Internet users continues to increase along with the development of devices smartphones/PDAs (Personal Digital Assistance), e-commerce and social media. Internet traffic volume continues to rise encourage all providers to provide connections with a large transport capacity through technology broadband.Banyaknya number of operators and the growth of broadband Internet customers require mapping of the segment as a basis for marketing activities. Segmentation parse a heterogeneous market into homogeneous groups according to the elements of geography, demographics, behavior and psikografi.Dalam this survey, segmentation based on demographic factors with the variables age, sex (gender), education, monthly expenditure (SES) and internet service providers . Segmentation is done through a survey conducted in several big cities in Indonesia with the cluster sampling method. The survey results showed that the level of Internet usage between men and women are relatively equal, so the aspect of gender did not significantly affect the process of offering Internet services. While education and SES variables have positive correlation with the level of usage (usage) internet. Other findings showed that the category of heavy internet users (heavy users) are dominant, with a percentage> 50% in nearly all surveyed operators.